Factors Hindering Tourism Industry Development: Gambella People2019;s National Regional State, South West Ethiopia (Global Journal of Management and Business Research, 2019)
Tourism is a circulation of people who travel to or stay in places outside their home country It has being believed as a major ingredient in the economic development strategy However various external and internal factors have been affecting the sustainable development of the tourism industry worldwide Although Ethiopia possesses numerous natural religious historical non-natural and cultural tourism attractions economic contribution and its potential are incomparable Shortage of tourist facilities lack of skillful human resources weak promotion lack of integration and political will are the major negatively contributing forces Although Ethiopia possesses massive tourism development potentials with its unique biodiversity and spectacular topographic features its economic contribution to the country is unmatched Similarly Gambella Region has endowed with tourism potentials But its tourism industry development is in an infant stage Nevertheless a limited study has done in identifying factors hindering the development of the tourism industry in the region
Keywords: tourism; tourism industry; constraints; gambella; Ethiopia